2016
DOI: 10.1504/jdr.2016.079763
|View full text |Cite
|
Sign up to set email alerts
|

Design for sustainable behaviour: a case study of using human-power as an everyday energy source

Abstract: Abstract:There is an increased focus on research identifying design strategies to influence user behaviour towards more sustainable action, known as Design for Sustainable Behaviour (DfSB). Recent literature in this field has introduced a number of design processes, and developed a model that emerged through consensus. However, not enough case studies are accompanied by those proposed strategies; therefore it is difficult to evaluate their effectiveness. This paper presents findings from a case study of induci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…The main objective of this edition of the integrative design class was to employ the concept of Design for Sustainable Behavior (DfSB) [41,42], based on reducing its negative impact on the natural environment, caused by the unreflective conduct of buildings' users, as well as to persuade the occupants to behave in a more environmentally responsible way through the carefully designed products. Since interior components make for structurally, formally, and functionally developed products, this concept can be applied to their creation process.…”
Section: Case Studymentioning
confidence: 99%
“…The main objective of this edition of the integrative design class was to employ the concept of Design for Sustainable Behavior (DfSB) [41,42], based on reducing its negative impact on the natural environment, caused by the unreflective conduct of buildings' users, as well as to persuade the occupants to behave in a more environmentally responsible way through the carefully designed products. Since interior components make for structurally, formally, and functionally developed products, this concept can be applied to their creation process.…”
Section: Case Studymentioning
confidence: 99%
“…21 With this decline in PA, it is imperative and a crucial timely issue given the current increased levels of children’s ST. 22 Thus, numerous studies have investigated the need for using the technology-related intervention to reduce the said behavior. For instance, Shin and Bhamra 23 evaluated the concept of utilizing human-powered products to induce PAs at home, using an exercise bike to power the television. His study concluded that the financial gain of using human power as an alternative power source was inadequate and further emphasized that the potentiality of such intervention would be more lucrative when used as means to increase PA and reduce sedentary behavior in the home environment.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies have focused on identifying design strategies to bring about a behavioural change for achieving environmental benefit [5][6][7][8]. More recently, a number of empirical data are being reported that evaluated the acceptance and effectiveness of these strategies through case studies [9][10][11] that were focussed on strategy selection for targeted behaviour [12][13][14]. Further theoretical development has been made to improve its design methodologies, processes and toolbox, incorporating behavioural psychology and the consideration of ethical implications [15][16][17][18][19].…”
Section: Background-dimension Of Power In Decision Makingmentioning
confidence: 99%
“…Firstly, building on existing work linking human generated energy power to electricity consumption [11], the authors have an ongoing longitudinal study that investigates the effectiveness of the framework, focusing on instigating a daily exercise habit for people feeling physically inactive. The design-led intervention includes features relating to each dimension, providing empowerment via an exercise routine (or force exercise via constraining peripheral activity such as TV watching), feedback display indicating long and short-term consequences of changing behaviour (feedback and forward), and evaluation of the internalisation process through periodic qualitative interviews with the study participants; see [11] as an example. The internalised behaviour can be instigated through gradually delegating more empowerment of exercise to the user rather than by using force, causing the user to set daily exercise goals and make the behaviour itself be intrinsically rewarding (healthy).…”
Section: Practical Implication Of the Three Dimensions Of Dfsbmentioning
confidence: 99%